Exploring the roots of filial obligations: a comparative analysis of Confucian and Western perspectives - Woon, Meryl Xi Lu (Nanyang Technological University, 2023)
There are distinguishable features in how the Confucian and Western tradition conceptualize the nature of filial obligations as a moral propensity. The focus of this essay is to examine the two perspectives on filial obligations and show how the Confucian tradition of filial piety presents a more cohesive and compelling account than the Western tradition. Confucianism stresses on the importance of cultivating human-heartedness as a pre-requisite for people to attain moral virtuousness and filial obligations become intrinsically motivated through this process of self-cultivation. For the Western accounts of filial duties, I draw reference from the Debt Theory, Gratitude Theory, Friendship Theory, and the Special Goods Theory. I explore these accounts to illuminate the underlying presuppositions which render filial obligations as being extrinsically motivated.